2013
DOI: 10.1074/jbc.m113.487561
|View full text |Cite
|
Sign up to set email alerts
|

An Intrinsically Disordered Photosystem II Subunit, PsbO, Provides a Structural Template and a Sensor of the Hydrogen-bonding Network in Photosynthetic Water Oxidation

Abstract: Background:PsbO is an intrinsically disordered subunit of photosystem II. Results: Temperature-sensitive PsbO dynamics are identified by reaction-induced Fourier transform infrared spectroscopy and the removal and reconstitution of PsbO. Conclusion: PsbO serves as an organizational template and undergoes flash-induced hydrogen-bonding changes, coupled with the catalytic cycle of water oxidation. Significance: PsbO samples a rough conformational landscape when bound to its target, the photosystem II reaction ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 110 publications
3
30
0
Order By: Relevance
“…The possibility of such long‐range effects on the FTIR differential spectra is also in line with PsbO, PsbP and PsbQ depletion experiments (Offenbacher et al , Ifuku and Noguchi ), reporting a strong dependence of the spectra on the S state. These proteins are involved in water delivery and proton channels Shutova et al (), therefore may differ in different states.…”
Section: Introductionsupporting
confidence: 73%
“…The possibility of such long‐range effects on the FTIR differential spectra is also in line with PsbO, PsbP and PsbQ depletion experiments (Offenbacher et al , Ifuku and Noguchi ), reporting a strong dependence of the spectra on the S state. These proteins are involved in water delivery and proton channels Shutova et al (), therefore may differ in different states.…”
Section: Introductionsupporting
confidence: 73%
“…[42][43][44]46 It should be noted that although it was recently reported that the removal of PsbP and PsbQ from PSII core preparations of spinach showed no significant effect on the S 2 /S 1 spectrum, 73 the control S 2 /S 1 spectrum in ref 73 exhibited a typical amide I feature of PsbP-depleted PSII, i.e., lower and higher intensities for the 1668 and 1686 cm −1 peaks, respectively (compare the spectrum of Figure 4A in ref 73 with our spectra of Figure 1b in ref 42). Hence, it is suggested that the intact PSII core complexes from spinach in ref 73 were actually depleted of the PsbP and PsbQ proteins when FTIR spectra were measured, possibly because of the presence of potassium ferricyanide in addition to 20 mM CaCl 2 . The latter work also showed that removal of PsbO significantly affected the amide I bands of the S 2 /S 1 difference spectrum, 73 whereas our previous measurements showed that PsbO depletion did not induce further changes in the amide I bands of PsbP-and PsbQ-depleted PSII membranes.…”
Section: ■ Discussionmentioning
confidence: 97%
“…This allows PsbO to respond dynamically to changes in the abundance of redox‐active thioredoxin (Roberts et al ), pH (Shutova et al , , , Bommer et al ), GTP (Lundin et al ) and the calcium ions (Heredia and De Las Rivas , Shutova et al , Murray and Barber ). The structural dynamics of PsbO have been analyzed and related to its functional role in photosynthetic water oxidation based on experiments using intra‐molecular cross‐linking (Enami et al ) and FTIR spectroscopy (Hutchison et al , Sachs et al , Offenbacher et al ). The substrate water exchange in PSII depends on the presence of the extrinsic proteins and the removal of PsbO has slightly different effect in prokaryotic and eukaryotic organisms (Hillier et al ).…”
Section: Introductionmentioning
confidence: 99%